Structural differences of starch-proteolyzed peptide complexes dictate in vitro fermentation behavior: Selective regulation of gut microbiota composition and short-chain fatty acid production - Xiang Huang; Hui Yang; Rong Feng; Yue Li; Song Zhu; Dejian Huang (Food Hydrocolloids, 2027)

Exploration of shared gene signatures and molecular mechanisms between psoriasis and COVID-19: evidence from transcriptome data - Rong-Jing Dong; Lu-Hui Yang; Yu-Ye Li; You-Wang Lu (Mammalian Genome, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Multi-copy expression of classical swine fever virus E2 in a recombinant pseudorabies virus enhances immunogenicity and supports its potential as a PRV-CSFV bivalent vaccine candidate - Xianfei Shang; Hui Zhao; Yufeng He; Zhenxiang Rong; Xiquan Ke; Jinglei Gao; Ke Zhang; Jiyuan Luo; Min Zhang; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

The microalgae-bacteria symbiotic inoculation enhances sandy soil multifunctionality and wind erosion resistance through microbial network reorganization - Lianhao Sun; Xin Sun; Haonan Zhang; Hui Nie; Chong Li; Xin Liu; Haidong Li; Xiongfei Zhang; Qianqian Liu; Jingyi Zeng; Weiqi Meng; Guoshuai Hou; et al. (CATENA, 2026)

Underestimated climate contributions: Dynamic attribution of vegetation changes in China incorporating soil moisture and vapor pressure deficit - Hui Zheng; Yuhang Huang; Rong Li; Xiaoshan Yin; Bolin Fu; Junling Jin (Agricultural and Forest Meteorology, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

Phosphorus limitation and manganese toxicity induced by high nitrogen inputs suppress plant biomass - Jiapu Li; Xuebin Yan; Jordi Sardans; Josep Peñuelas; Shiting Hong; Peng Wang; Pinwei Zhang; Rong Song; Yanwen Zhao; Yong Li; Hui Guo (Plant and Soil, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

A new benzoate derivative from Talaromyces fusiformis , an endophytic fungus cultured from Hypecoum leptocarpum Hook. f. et. Thoms - Cai-xia Li; Ting An; Hui Tan; Rong Guo; Huai-Xiu Wen (Natural Product Research, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Burkholderia cepacia NB-13: Biocontrol efficacy and medium-driven metabolic regulation - Zhou Yin; Xiaoqin Li; He Guan; Dindi Tu; Xingyi Luo; Wancheng Hu; Fanqian Zhou; Menglong Li; Shulin Liu; Hui Li; Rong Song; Kailin Liu; et al. (Pesticide Biochemistry and Physiology, 2026)

Acquisitive, diverse tree stands resist vine invasion via contrasting temporal effects on crown volume and herb cover - Li Zhang; Liting Zheng; Marc W. Cadotte; Charles A. Nock; Baiyu Yang; Zhiming Hu; Ciliang Zhao; Wen-Hui You; En-Rong Yan (Forest Ecology and Management, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Illumination-induced restructuring of extracellular polymeric substances from Klebsiella Sp. HDJY-1 drives indirect photodegradation of thifensulfuron-methyl - Jiaying Gu; Yaqi Jiao; Chunnan Zhou; Junxin Jia; Siming Li; Kai Wang; Hui Li; Hongtao Shi; Qin Zhou; Rong Liu; Li Li (Water Research, 2026)

Comparative metagenomics of three distinct biological soil crusts in sandy land of Northern China - Rong Hui; Yalin Zhou; Hongxia Zhang; Huijuan Tan; Xinrong Li (Plant and Soil, 2026)

Position-sequence enhanced meta-reinforcement learning with adaptive fine-tuning for few-shot GNSS positioning correction - Zhenni Li; Hui Li; Jianhao Tang; Rong Yuan; Xuesong Tan; Maodeng Li; Shengli Xie (GPS Solutions, 2026)

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

A joint optimization method for weight estimation and re-identification based on a cattle back semantic disentanglement model - Yuqi Zhang; Longxiang Li; Hui Kang; Shiyuan Liang; Kai Niu; Yue Rong; Zhiqiang He (Computers and Electronics in Agriculture, 2026)

Sensitivity analysis and multi-objective particle swarm optimization (MOPSO) of a hollow fiber membrane module for the solar-based heating and humidification system - Si Zeng; Peng Peng; Nan-Feng Li; Cai-Hang Liang; Rong-Hui Qi; Yan-fang Dong; Yu-Kui Men; Jia-Hui Li; Gui-Yin Li (Energy and Buildings, 2026)

Evaluation of protein and metabolic engineering strategies on (−)-α-bisabolol production by Escherichia coli - Jiayi Ma; Rong Fang; Xiaoyuan Yue; Hui Jiang; Qixuan Kong; Tiankuo Jiang; Jiale Yu; Chang Zhou; Yuanyuan Xia; Wei Shen; Haili Liu; Yaqin Shen; et al. (Systems Microbiology and Biomanufacturing, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Tarsus-enriched chemosensory proteins in Achelura yunnanensis (Lepidoptera, Zygaenidae) and their interactions with pesticides - Fu-Peng Li; Zi-Hui Liu; Xiao-Rong Xiong; Jin-Lan Zhang; Hai-Yan Xiao; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Effects of recovered exogenous nitrogen addition on pilot-scale single-cell protein production from soybean soaking water - Hui Xu; Yingqiu Pu; Li Wang; Rong Huang; Yan Zhou (Bioresource Technology, 2026)

Metallogenic Age of the Qianjiadian Uranium Deposit—Evidence from Fluid Inclusions and (U-Th)/He - Ruxin Ding; Yangshijia Li; Zilong Li; Rongli Huang; Minqiang Cao; Xingzhou Chen; Hui Rong; Heping Zou (Journal of Earth Science, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

Coordination-tailored conductive metal-organic frameworks boost CO2 electroreduction to ethylene for cascade ethylene glycol production - Hui Guo; Shao-Shuai Zhao; Duan-Hui Si; Weijin Li; Zi-Ao Chen; Rong Cao; Roland A. Fischer; Yuan-Biao Huang (Science Bulletin, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Lattice distortion-driven electronic engineering of high-entropy alloys for efficient polysulfide catalysis in LiS batteries - Li Zhang; Yan Wang; Bo-Wen Lin; Rong-Rong Liang; Tian-Hui Dang; Zhuo Zhao (Chemical Engineering Journal, 2026)

Comprehensive genomic analysis of the maize ACP gene family reveals ZmACP1-mediated salt stress tolerance in Arabidopsis - Yunhao Wu; Junyu Chen; Hanqiu Ge; Xing Rong; Yuchen Wang; Meiwang Zhang; Zhigang Li; Yingrui Xi; Junfeng Tang; Junyi Li; Ping Li; Baohua Wang; et al. (Plant Cell Reports, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Regulating coordination environment of vanadate cathode for ultralong lifespan zinc-ion batteries - Tingting Lv; Rong Li; Linyu Yang; Shuying Wang; Kunjie Zhu; Jiadong Wu; Hui Yao; Haibing Li; Kamal Toqtarhan; Hongyu Mi; Anqiang Pan (Chemical Engineering Journal, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Fabrics of forsterite in CBa chondrite Sierra Gorda 013 - Rong Li; Wei Chen; Chun-Hui Li (Acta Geochimica, 2026)

CRODNet: Cascaded learning network for contactless top-view cattle rotated object detection - Hui Kang; Yuqi Zhang; Longxiang Li; Chunyang Li; Sen Wang; Kai Niu; Yue Rong; Zhiqiang He (Computers and Electronics in Agriculture, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Distribution and potential drivers of methane emissions from deep-sea environments in Haima cold seep areas - Li Tang; Jing-Chun Feng; Can-Rong Li; Xiao Chen; Hui Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Introduction Tracing methane originating from deep-sea environments is essential for understanding the global methane budget. However, knowledge regarding the mechanisms governing methane transfer from deep-sea sediments to the water column in cold seep environments remains limited. This study aims to quantitatively investigate the distribution of methane and identify its controlling factors within the Haima cold seep areas. Methods A comprehensive analysis was conducted to investigate the distribution characteristics of methane and its potential drivers in both the water column and sediment porewaters within the Haima cold seep areas. Results The key findings are: (1) Haima cold seeps serve as a methane source to the atmosphere, with pronounced spatial heterogeneity in emission strength across the monitored regions. (2) The vertical distribution of methane is influenced by multiple environmental factors. Key factors in sediment porewaters include sediment depth, porosity, inorganic carbon (IC), chloride (Cl – ), and sulfate (SO 4 2– ), whereas silicate (SiO 3 2– ) and dissolved oxygen (DO) are primary regulators in the water column. (3) Sediments represent a significant methane source for bottom seawater, with methane consumption being more pronounced in seepage areas than in non-seepage areas. Discussion This study demonstrates that methane dynamics in the Haima cold seep are complex and driven by a combination of physical, chemical, and biological processes across the sediment–water interface. The identified key drivers underscore the importance of porewater geochemistry and water column biogeochemistry in controlling methane release. These findings significantly advance our understanding of methane transport in deep-sea seep systems and provide crucial insights for refining global methane flux estimates.

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Wood-derived self-standing carbon electrodes for electrocatalysis: design, performance, and prospects - Liu-Liu Shen; Xinkun Li; Peiran Wu; Jiansong Wang; Hui Yu; Yipu Xu; Yuhang Wang; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2025)

Erosion rates of yardang landforms downstream of the Peacock River, NW China - Bai Youliang; Bo Li; Jinhong Rong; Hui Chen; Jinming Zheng; Jianshe Liu; Tan Bao; Jiangnan Jin; Chuan Wang (Journal of Sedimentary Environments, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Hydrochemical characteristics and circulation pattern of fault-type geothermal water in karst region: A case study in western Yunnan, China - Chuan Wen; Wenping Mu; Qiang Wu; Zhen Yang; Rong Li; Yubing Song; Hui Tan (Geothermics, 2025)

How root exudates of vegetation contribute to prevention and control of soil disintegration on Chinese Loess Plateau: A case study of Robinia pseudoacacia L. - Tao Xiao; Ping Li; Rong Jiang; Sai K. Vanapalli; Xiangcheng Han; Hui Zhai; Yiyi Yang; Qi Gu; Jiading Wang (Engineering Geology, 2025)

Protective effects of melatonin pretreatment on oxidative damage and immune system impairment in Eriocheir sinensis exposed to ammonia-N stress: insights from the intestine-hepatopancreas axis - Rui Wang; Hui Peng; Dapeng Li; Rong Tang (Aquaculture International, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Identification and Functional Analysis of Trehalose Synthesis Genes in Foxtail Millet: Insights into Low-Temperature Stress Response - Yueyue Wang; Yajun Li; Yidan Luo; Yuhua Xu; Bo Zhao; Rong Sun; Juan Zhao; Xukai Li; Yijuan Zhang; Yuanhuai Han; Hongying Li; Hui Zhang (Journal of Plant Growth Regulation, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Complete genome of Thalassotalea piscium NK451B, an Antarctic bacterium with abundant extracellular proteases - Jia-Yi Song; Zi-Ying Li; Xiao-Hui Yang; Jin-Rong Wei; Kang Li; Yi Zhang (Marine Genomics, 2025)

Human activity driven spatial heterogeneity of pollutants in a highland river basin revealed by non-target screening and improved PBT evaluation: A case study from the Yalong River on the Qinghai-Tibet Plateau,China - Zhiyuan Ma; Shunlong Meng; Xin Gao; Hui Wan; Longxiang Fang; Lei Zhu; Zhonghua Li; Yuxiao Gao; Liping Qiu; Bo Rong; Chao Song (Journal of Hazardous Materials, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Corrigendum to “Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes” [J Hazard Mater 489 (2025) 137706] - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

All-weather highly efficient degradation of persistent organic pollutants over RhB-sensitized BiOCl under natural sunlight - Wen Sun; Chunping Su; Wei Zhang; Hui Li; Huiping Zhao; Rong Chen (Journal of Environmental Chemical Engineering, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

Histopathological Insights into Demyelination and Remyelination After Spinal Cord Injury in Non-human Primates - Junhao Liu; Zucheng Huang; Kinon Chen; Rong Li; Zhiping Huang; Junyu Lin; Hui Jiang; Jie Liu; Qingan Zhu (Neuroscience Bulletin, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Ambient air pollution and the risk of cancer: Evidence from global cohort studies and epigenetic-related causal inference - Dong Peng; Xiao-Yu Liu; Yuan-Hui Sheng; Si-Qi Li; Dan Zhang; Bo Chen; Pei Yu; Zhao-Yuan Li; Shuai Li; Rong-Bin Xu (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Nrf2 Ameliorates Sevoflurane-Induced Cognitive Deficits in Aged Mice by Inhibiting Neuroinflammation in the Hippocampus - Junhua Li; Jinfeng Li; Yafang Liu; Chuwen Hu; Hui Xu; Dong Cao; Rong Zhang; Kun Zhang (Molecular Neurobiology, 2025)

Corrigendum to ‘Carbon black nanoparticles induce pulmonary fibrosis through NLRP3 inflammasome pathway modulated by miR-96 targeted FOXO3a’ [Chemosphere (2020) 125075] - Lixiao Zhou; Peiyuan Li; Mengyue Zhang; Bin Han; Chen Chu; Xuan Su; Binghua Li; Hui Kang; Jie Ning; Boyuan Zhang; Shitao Ma; Dong Su; et al. (Chemosphere, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Steering CO2 electroreduction to hydrocarbons over 2D thiol-based conductive metal-organic framework - Qiu-Jin Wu; Duan-Hui Si; Yu-Liang Dong; Qian Chen; Li-Li Han; Rong Cao; Yuan-Biao Huang (Science Bulletin, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Round-the-clock Cr(VI) removal from actual industrial electroplating wastewater over Bi2S3/PDA/PEI under natural conditions: Synergism of adsorption and photocatalysis - Li Song; Chunping Su; Hui Li; Huiping Zhao; Rong Chen (Chemical Engineering Journal, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Effect of scenting process on the taste profile of jasmine green tea and the potent bitterness-enhancing compound in jasmine flowers - Jia-Ying Chen; Wen-Wen Luo; Wen-Xuan Li; Ya-Nan Zheng; Xin-Qiang Zheng; Jian-Liang Lu; Yue-Rong Liang; Jian-Hui Ye (Food Research International, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

The influence of carbon dioxide on fermentation products, microbial community, and functional gene in food waste fermentation with uncontrol pH - Xin-Rong Pan; Pei-Ken Shang-Guan; Shu-Hui Li; Chu-Hao Zhang; Jia-Min Lou; Liang Guo; Lu Liu; Yin Lu (Environmental Research, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

Performance prediction of urban tunnel purification system based on the verified random number screening algorithm - Jie Xia; Hao-Yi Zhao; Hui Ren; Long Chen; Fang Li; Wei-Rong Shi; Yi-Song Xie; Mei-Lan Tan; Fei Li; Bin Zhou (Sustainable Cities and Society, 2025)

Investigating the matrix effect of high/low methoxyl pectins on typical aroma of apple juice using HS-SPME-GC–MS and NMR analysis - Wan Qing Li; Hui Liu; Yu Rong Guo; Xiao Yu Wang; Peng Tao Zhao (Food Chemistry, 2025)

Variation in microbial communities and network ecological clusters driven by soil organic carbon in an inshore saline soil amended with hydrochar in Yellow River Delta, China - Hui Yao; Yadong Cheng; Qingxian Kong; Xiao Wang; Ziguo Rong; Yue Quan; Xiangwei You; Hao Zheng; Yiqiang Li (Environmental Research, 2025)

Characterization of Gut Microbiota in Rats and Rhesus Monkeys After Methamphetamine Self-administration - Li He; Jia-hui Zhou; Huan Li; Wen-lei Zhang; Tie-qiao Liu; Hai-feng Jiang; Rong-wei Zhai; Xiao-jie Zhang (Molecular Neurobiology, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Cascading impacts of nitrogen deposition on soil microbiome and herbivore communities in desert steppes - Jingxi Liu; Mengmeng Zhu; Xiangfeng Shi; Cang Hui; Yurong Sun; Rong Zhang; Decai Jin; Zhihong Li; Honghao Chen; Zihua Zhao (Science of The Total Environment, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Facile engineering of metal–organic framework derived SnO2@NiO core–shell nanocomposites based gas sensor toward superior VOCs sensing performance - Hui Xu; Haoran Zhong; Jinwu Hu; Xianjun Rong; Wenhui Zhang; Yinsheng Wang; Shengjuan Li; Guisheng Li; Ding Wang (Chemical Engineering Journal, 2024)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

The effect of Desulfovibrio caledoniensis and Pseudomonas aeruginosa on the corrosion behaviour of 70Cu-30Ni alloy - Li-Jun He; Zheng-Hui Qiu; Shao-Xia Ma; Rong-Chang Zeng; Cun-Guo Lin (Biofouling, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Robust polymer electrolytes with fast ion-transport nanochannels constructed by carbon dots for long lifespan Li metal batteries - Jia-Wen Ni; Xi-Rong Zhang; Tian-Bing Song; Zun-Hui Huang; Qian-Li Ma; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

On-demand detachable and reuseable adhesives assembled by organic-silicon nanogels with wide applicability and excellent harsh-environment resistance - Hui Rong; Pengwei Zhao; Manhua Lu; Liandong Deng; Shuangyang Li; Xiaobin Fan; Zhanpeng Ye; Jianhua Zhang; Anjie Dong (Chemical Engineering Journal, 2024)

Accelerated cartilage regeneration through immunomodulation and enhanced chondrogenesis by an extracellular matrix hydrogel encapsulating Kartogenin - Kai Huang; Qing-Yi Zhang; Jie Tan; Rong Nie; Zi-Yuan Feng; Yuan Liu; Ning Sheng; He-Xi Li; Yue-Qi Zhang; Bin Shen; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Chemical constituents from Croton lauioides Radcl.-Sm. & Govaerts and their chemotaxonomic significance - Jia-Xin Hu; Qian Liang; Li-Lin Xiao; Rong-Lin Jia; Xiao-Min Su; Wen-Hui Xu (Biochemical Systematics and Ecology, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

Effects of low-temperature stress on serum biochemical indicators, intestinal microbiome, and transcriptome of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Aquaculture International, 2024)

Ti2TaC2: A novel out-of-plane ordered MXene towards flexible and cytocompatible supercapacitors - Yunfeng Guan; Lixian Jiang; Rong Zhao; Xuanke Li; Hui Zhu; Qin Zhang; Zhijun Dong; Nianjun Yang; Ye Cong (Chemical Engineering Journal, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Suitable habitat evaluation and ecological security pattern optimization for the ecological restoration of Giant Panda habitat based on nonstationary factors and MCR model - Hui He; Xiangke Yu; Hui Yu; Zhigang Ma; Yong Luo; Tao Liu; Ziwei Rong; Jinhong Xu; Dianpeng Chen; Pengshang Li; Fuxin Yuan; Yongtao Zhao (Ecological Modelling, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

A deep learning network for improving predictions of maximum and minimum temperatures over complex terrain - Lin Xu; Li Zhou; He Chen; Rong-Hui Cai; Yue Zhou (Theoretical and Applied Climatology, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Iron transformation and hydroxyl radical production during mixing surface water and groundwater in the riparian zone: Effects of bicarbonate and surface water-groundwater ratio - Shuang Li; Yao Huang; Junhao Shen; Shengjun Mao; Rong Peng; Hui Liu (Applied Geochemistry, 2024)

Metabolome and transcriptome reveal high abundance of bioactive substances in albino jujube fruit as potential function food - Yang Wang; Yong Huang; Panhui Song; Xuemei Peng; Xinyu Li; Rong Su; Hui Zhang; Lijin Lin; Hui Xia; Qunxian Deng (Food Bioscience, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Expression analysis and antiviral activity of koi carp (Cyprinus carpio) viperin against carp edema virus (CEV) - Xiao-wen Wang; Rong Zhang; Li-li Liu; Hui-juan Li; Hua Zhu (Fish & Shellfish Immunology, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

Chronic Pb exposure impairs learning and memory abilities by inhibiting excitatory projection neuro-circuit of the hippocampus in mice - Rong-Xin Zou; Xiaozhen Gu; Chenqing Huang; Hui-Li Wang; Xiang-tao Chen (Toxicology, 2024)

Automatic and adaptive picking of surface-wave dispersion curves for near-surface application - Hui Liu; Jing Li; Rong Hu (Journal of Applied Geophysics, 2024)

Flexural behavior of wet panel-to-panel groove-and-tongue joints provided with lapped U-bars - Ao Dong; Zhenyu Li; Bin Rong; Changxiang Wang; Zeming Wang; Hui Xu (Engineering Structures, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

A Multi-Task Learning Based Runoff Forecasting Model for Multi-Scale Chaotic Hydrological Time Series - Hui Zuo; Gaowei Yan; Ruochen Lu; Rong Li; Shuyi Xiao; Yusong Pang (Water Resources Management, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Enantioselective effect of the chiral fungicide tebuconazole on the microbiota community and antibiotic resistance genes in the soil and earthworm gut - Chao-Feng Li; Yi-Rong Zhang; Zhen-Chao Tan; Hui-Juan Xu; Cheng-Lan Liu (Science of The Total Environment, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Positive relationships between species diversity and genetic diversity on a local scale at Mt. Wu Yi, China - Lei Xie; YueYao Feng; Rong Zhao; Ting Lv; NingJie Wang; Yao Li; Xiao Zheng; ShuiFei Chen; Hui Ding; YanMing Fang (Biodiversity and Conservation, 2023)

High phytoplankton diversity in eutrophic states impedes lake recovery - Rong Wang; C. Patrick Doncaster; Wenxiu Zheng; Min Xu; Hui Yang; Yun Li; Yongjiu Cai; Yanjie Zhao; Enlou Zhang; Xiangdong Yang; Boqiang Qin (Journal of Biogeography, 2023)
Aim The widely observed positive response of productivity to biodiversity, known as the biodiversity‐productivity relationship (BPR), underpins nature‐based solutions for mitigating and adapting to global changes. Little is known of the role of such emergent processes in the restoration of damaged ecosystems. Here, we test for evidence of a BPR in degraded freshwater lakes, and its role in underpinning or undermining lake recovery from eutrophic states. Location Lower Yangtze and Huaihe river basins, China, East Asia. Taxa Freshwater phytoplankton; also macrophytes, fish, zooplankton and zoobenthos. Methods A systematic review of biodiversity studies was conducted to enumerate freshwater biodiversity change during eutrophication, encompassing 572 samples from 155 lakes in East China. Empirical samples were then taken of 93 phytoplankton communities from 38 lakes in ecologically degraded states of eutrophication. Samples were analysed for niche overlap in relation to biodiversity and productivity, and metrics of network structure indicative of community stability. Results Reviewed publications on eutrophication in East China lakes revealed losses in biodiversity of macrophytes, fishes, zooplankton and zoobenthos but not phytoplankton. Empirically sampled eutrophic lakes maintained high phytoplankton biodiversity through niche differentiation, and phytoplankton biodiversity correlated positively with biomass, in line with the expectations of BPR. Conclusions The positive effect of biodiversity on phytoplankton productivity in eutrophic lakes acts in opposition to the negative impacts on productivity induced by eutrophication‐management strategies of nutrient suppression. In degraded systems, the BPR contributes to sustaining productivity of lake phytoplankton communities, impeding recovery from a eutrophic state. This is a case of the BPR playing an undesirable role at the ecosystem level. Lake recovery programmes need to anticipate that the control of phytoplankton biomass will depend on reducing nutrients to a level sufficient to degrade the internal structure of the phytoplankton community.

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Progress and perspective in enrichment and separation of radionuclide uranium by biomass functional materials - Jia Lei; Huanhuan Liu; Li Zhou; Yazhou Wang; Kaifu Yu; Hui Zhu; Bo Wang; Mengxuan Zang; Jian Zhou; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Soil-water characteristic surface model of soil-rock mixture - Kui Wang; Ying Hui; Chuan Zhou; Xue Li; Yao Rong (Journal of Mountain Science, 2023)

Corrigendum to “Divergent responses of moss- and lichen-dominated biocrusts to warming and increased drought in arid desert regions. Agricultural and Forest Meteorology, 303 (2021) 108387 - Xinrong Li; Rong Hui; Peng Zhang; Naiping Song (Agricultural and Forest Meteorology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Mechanisms and adsorption capacities of ball milled biomass fly ash/biochar composites for the adsorption of methylene blue dye from aqueous solution - Huaiyan Li; Jie Kong; Haiting Zhang; Jiale Gao; Yan Fang; Jiaqi Shi; Tao Ge; Ting Fang; Yanhong Shi; Rong Zhang; Ningyuan Zhang; Xinju Dong; et al. (Journal of Water Process Engineering, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Chemical weathering in the Himalayan system in response to the evolution of the Indian summer monsoon since 37 ka - Long Tan; Jianguo Liu; Yun Huang; Rong Xiang; Shengfa Liu; Hui Zhang; Jingrui Li; Linghui Yu; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Genome resequencing reveals genetic loci and genes conferring resistance to SMV-SC8 in soybean - Jiahao Chu; Wenlong Li; Zhanwu Yang; Zhenqi Shao; Hua Zhang; Shaoda Rong; Youbin Kong; Hui Du; Xihuan Li; Caiying Zhang (Theoretical and Applied Genetics, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Degradation of polymeric polyproanthocyanidins from black chokeberry by microwave-assisted nucleophilic technique of sulfite/catechin: Reaction kinetics, antioxidation and structural analysis - Miao Li; Pu Li; Yufeng Xu; Baiqing Zhang; Jinfeng Li; Weitian Zhong; Hui Zang; Hui Zheng; Haifeng Rong; Fengming Ma (Food Chemistry, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

A comparative study of soil nutrient availability and enzyme activity under biological soil crusts in different erosion regions of the Loess Plateau, China - Rong Hui; Huijuan Tan; Xinrong Li; Ruiming Zhao; Haotian Yang (Plant and Soil, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Effects of low-temperature stress on intestinal structure, enzyme activities and metabolomic analysis of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Frontiers in Marine Science, 2023)
Water temperature plays a crucial role in the growth, survival, and reproduction of fish species, as they make up the majority of aquatic fauna. In this study, the effects of low temperature were studied on the functional state of juvenile golden pompano ( Trachinotus ovatus ) under low-temperature stress. The study was conducted at 28°C in the control group and 18°C in the cold group for 14 d to determine the intestinal tissue, digestive and antioxidant enzyme activities, and metabolites of juvenile fish. The results showed that: (1) the swelling degree of the muscle layer deepened and was congested with a longer low-temperature stress period. The folds were sparse, from slight swelling to shedding and deformation. The intestinal mucosa was necrotic and had vacuoles, and the number gradually increased. Serious erosion of the villi occurred. (2) The specific activities of digestive enzymes showed a downward trend. (3) The intestinal superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, and glutathione peroxidase (GSH-Px) activity showed an upward trend. The intestinal catalase (CAT) activity showed a downward trend. (4) Compared with the control group, there were 28 metabolites in the cold group showing significant differences, among which Z, 11Z, 14Z-eicosatrienoic acid, stearic acid, and adrenic acid showed an upward trend. In contrast, spermidine and uracil showed a downward trend. Among the enriched metabolic pathways, the main differential pathways were unsaturated fatty acid biosynthesis, fatty acid biosynthesis, linoleic acid metabolism, pyrimidine metabolism, and β-alanine metabolism. According to metabolomic analysis, under low-temperature stress, the fish body improved the synthesis of unsaturated fatty acids and saturated fatty acids to adapt to a low-temperature environment and consumed spermidine to improve its immune ability to clear the peroxide generated by the synthesis of unsaturated fatty acids in the body so that the cells were protected from oxidative damage. After 14 days, low-temperature stress affected metabolites and enzyme activity indices in juvenile golden pompano. Low-temperature stress causes changes in intestinal antioxidants and digestive enzymes and damage intestinal tissues. As a result of this exploration of how low temperatures affect the juvenile golden pompano, the foundation is laid for future studies, such as the molecular mechanisms of low-temperature adaptation in fish species.

Novel polysaccharide from Panax notoginseng with immunoregulation and prebiotic effects - Hui-Rong Yang; Xue Li; Hao Liu; Dong-Rui Zhao; Ying-Jie Zeng (Food Bioscience, 2023)

Rapid charge transfer in covalent organic framework via through-bond for enhanced photocatalytic CO2 reduction - Li-Juan Gong; Li-Yao Liu; Shao-Shuai Zhao; Shuai-Long Yang; Duan-Hui Si; Qiu-Jin Wu; Qiao Wu; Yuan-Biao Huang; Rong Cao (Chemical Engineering Journal, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Spatial distributions of intra-community tree species under topographically variable conditions - Ting Lv; Rong Zhao; Ning-jie Wang; Lei Xie; Yue-yao Feng; Yao Li; Hui Ding; Yan-ming Fang (Journal of Mountain Science, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Potential therapeutic strategies for myocardial infarction: the role of Toll-like receptors - Sumra Komal; Nimrah Komal; Ali Mujtaba; Shu-Hui Wang; Li-Rong Zhang; Sheng-Na Han (Immunologic Research, 2022)

MicroRNA-339-5p inhibits lipopolysaccharide-induced rat mesangial cells by regulating the Syk/Ras/c-Fos pathway - Jia Rong Gao; Miao Miao Shi; Hui Jiang; Xiao Li Zhu; Liang Bing Wei; Xiu Juan Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Molecular dietary analysis of Adélie (Pygoscelis adeliae) and Gentoo (Pygoscelis papua) penguins breeding sympatrically on Antarctic Ardley Island using fecal DNA - Yin-Xin Zeng; Hui-Rong Li; Wei Han; Wei Luo (Polar Biology, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Ventromedial Thalamus-Projecting DCN Neurons Modulate Associative Sensorimotor Responses in Mice - Jie Zhang; Hao Chen; Li-Bin Zhang; Rong-Rong Li; Bin Wang; Qian-Hui Zhang; Liu-Xia Tong; Wei-Wei Zhang; Zhong-Xiang Yao; Bo Hu (Neuroscience Bulletin, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Unloading Response Characteristics of Cross Fault Caverns: Effect of Fault Angles - Yong-Hui Shang; Lin-Rong Xu; Yong-Wei Li (Geotechnical and Geological Engineering, 2022)

The xyloglucan galactosylation modulates the cell wall stability of pollen tube - Qiqi Wei; Ying Yang; Hui Li; Zhiwen Liu; Rong Fu; Hanqian Feng; Chao Li (Planta, 2021)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Physiological response of moss/cyanobacteria crusts along a precipitation gradient from semi-arid to arid desert in China - Rong Hui; Xinrong Li; Ruiming Zhao; Huijuan Tan; Rongliang Jia (Plant and Soil, 2021)

Analysis on improvement effect of subgrade by dynamic compaction - Hui Qi; Chenjun Yang; Chao Hu; Yu Rong; Zhanyong Yao; Hongguang Jiang; Kai Yao; Luchuan Chen; Hui Li; Xianfei Teng (Arabian Journal of Geosciences, 2021)

Hippocampal Interneurons are Required for Trace Eyeblink Conditioning in Mice - Wei-Wei Zhang; Rong-Rong Li; Jie Zhang; Jie Yan; Qian-Hui Zhang; Zhi-An Hu; Bo Hu; Zhong-Xiang Yao; Hao Chen (Neuroscience Bulletin, 2021)
While the hippocampus has been implicated in supporting the association among time-separated events, the underlying cellular mechanisms have not been fully clarified. Here, we combined in vivo multi-channel recording and optogenetics to investigate the activity of hippocampal interneurons in freely-moving mice performing a trace eyeblink conditioning (tEBC) task. We found that the hippocampal interneurons exhibited conditioned stimulus (CS)-evoked sustained activity, which predicted the performance of conditioned eyeblink responses (CRs) in the early acquisition of the tEBC. Consistent with this, greater proportions of hippocampal pyramidal cells showed CS-evoked decreased activity in the early acquisition of the tEBC. Moreover, optogenetic suppression of the sustained activity in hippocampal interneurons severely impaired acquisition of the tEBC. In contrast, suppression of the sustained activity of hippocampal interneurons had no effect on the performance of well-learned CRs. Our findings highlight the role of hippocampal interneurons in the tEBC, and point to a potential cellular mechanism subserving associative learning.

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Accumulation and Depuration of Cd and its Effect on the Expressions of Metallothionein and Apoptotic Genes in Litopenaeus vannamei - Ling Li; Yu-Chun Shen; Jin-Rong Liang; Hu Liu; Tian-Ci Chen; Hui Guo (Bulletin of Environmental Contamination and Toxicology, 2021)

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

High diversity of planktonic prokaryotes in Arctic Kongsfjorden seawaters in summer 2015 - Yin–Xin Zeng; Wei Luo; Hui–Rong Li; Yong Yu (Polar Biology, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

High-frequency compensation for seismic data based on adaptive generalized S transform - Hui-Feng Li; Jin Wang; Zheng-Rong Wei; Fei-Long Yang (Applied Geophysics, 2020)

Inverse gaussian beam stack imaging in 3D crosswell seismic exploration of deviated wells and Its application - Fei-Long Yang; Chong Zhao; Zheng-Rong Wei; Hui Sun; Hui-Feng Li; Chi Zhao; Hao Luo (Applied Geophysics, 2020)

PSD-93 Interacts with SynGAP and Promotes SynGAP Ubiquitination and Ischemic Brain Injury in Mice - Qingxiu Zhang; Hui Yang; Hong Gao; Xiaomei Liu; Qingjie Li; Rong Rong; Zhenqian Liu; Xiu-e Wei; Liping Kong; Yun Xu; Liangqun Rong (Translational Stroke Research, 2020)

Water and salt stresses do not trigger bottom-up effects on plant-mediated indirect interactions between a leaf chewer and a sap-feeder - Yong-Cheng Dong; Zhi-Jian Wang; Rong-Yan Bu; Hui-Jie Dai; Li-Jun Zhou; Peng Han; Edwige Amiens-Desneux; Philippe Bearez; Nicolas Desneux (Journal of Pest Science, 2020)

NLRP6 contributes to inflammation and brain injury following intracerebral haemorrhage by activating autophagy - Han Xiao; Hui Chen; Rong Jiang; Li Zhang; Lu Wang; Hui Gan; Ning Jiang; Jing Zhao; Xuan Zhai; Ping Liang (Journal of Molecular Medicine, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

New Terpenoids And Lignans From The Twigs Of T ripterygium Hypoglaucum - Hui Zheng; Li Wang; Tao Yang; Dan Liu; Hong-Mei Li; Xuan-Qin Chen; Rong-Tao Li (Natural Product Research, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Molecular evolution of GII.P17-GII.17 norovirus associated with sporadic acute gastroenteritis cases during 2013–2018 in Zhoushan Islands, China - Can Chen; Bing Wu; Hui Zhang; Ke-Feng Li; Rong Liu; Hong-Ling Wang; Jian-Bo Yan (Virus Genes, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Transcript profiling of genes involved in carotenoid biosynthesis among three carrot cultivars with various taproot colors - Ya-Hui Wang; Tong Li; Rong-Rong Zhang; Ahmed Khadr; Yong-Sheng Tian; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Functional Analysis of Sheep POU2F3 Isoforms - Guang-Wei Ma; Yan-Kai Chu; Hua Yang; Xiao-Hong Yan; En-Guang Rong; Hui Li; Ning Wang (Biochemical Genetics, 2020)
POU domain class 2 transcription factor 3 (POU2F3) plays an important role in keratinocyte proliferation and differentiation. Our previous study identified four sheep POU2F3 transcript variants ( POU2F3-1 , POU2F3-2 , POU2F3-3 , and POU2F3-4 ), encoding three POU2F3 protein isoforms (POU2F3-1, POU2F3-2, and POU2F3-3). However, the functional differences among the three POU2F3 isoforms remain unknown. The objective of this study was to determine the tissue expression pattern of the four POU2F3 transcript variants in sheep and to investigate the functional differences in cell proliferation among the three POU2F3 isoforms. Quantitative RT-PCR analysis showed that the four POU2F3 transcripts were ubiquitously expressed in all tested adult sheep tissues, and POU2F3-1 exhibited higher expression level than the other three POU2F3 transcript variants in skin ( P P P P > 0.05). Dual luciferase reporter assays demonstrated that overexpression of any one of the three POU2F3 isoforms significantly inhibited the promoter activities of keratin 14 ( KRT14 ) and matrix metalloproteinase 19 ( MMP19 ) genes ( P KRT14 and MMP19 genes than POU2F3-1 and POU2F3-2 ( P P > 0.05). These results suggest three sheep POU2F3 isoforms have similar functional effects, but to a different extent.

Anfibatide Preserves Blood–Brain Barrier Integrity by Inhibiting TLR4/RhoA/ROCK Pathway After Cerebral Ischemia/Reperfusion Injury in Rat - Peng Gong; Rui Li; Hui-Yu Jia; Zheng Ma; Xiao-Yi Li; Xiang-rong Dai; Sheng-Yong Luo (Journal of Molecular Neuroscience, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

DNA methylation levels in different tissues in tea plant via an optimized HPLC method - Ying Gao; Jia-Li Hao; Zhen Wang; Kwan-Jeong Song; Jian-Hui Ye; Xin-Qiang Zheng; Yue-Rong Liang; Jian-Liang Lu (Horticulture, Environment, and Biotechnology, 2019)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

Two highly oxygenated Ergosterols from cultures of the Basidiomycete Conocybe siliginea - Chao-Jun Pu; Yue-Ling Peng; Zheng-Hui Li; Juan He; Rong Huang; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Quadruplex PCR detection of three quarantine Phytophthora pathogens of berries - Fang Liao; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Doudou Zhang; Jia-Feng Luo; Guan-Rong Li (European Journal of Plant Pathology, 2019)

Apparent Correlations Between AMPK Expression and Brain Inflammatory Response and Neurological Function Factors in Rats with Chronic Renal Failure - Li Yang; Ni-Rong Gong; Qin Zhang; Ya-Bin Ma; Hui Zhou (Journal of Molecular Neuroscience, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Loop-mediated isothermal amplification (LAMP) detection of Phytophthora hibernalis, P. syringae and P. cambivora - Guan-Rong Li; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Baohong Cao; Fang Liao; Jia-Feng Luo (Journal of Plant Pathology, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

The jasmonate-responsive transcription factor CbWRKY24 regulates terpenoid biosynthetic genes to promote saponin biosynthesis in Conyza blinii H. Lév. - Wen-Jun Sun; Jun-Yi Zhan; Tian-Run Zheng; Rong Sun; Tao Wang; Zi-Zhong Tang; Tong-Liang Bu; Cheng-Lei Li; Qi Wu; Hui Chen (Journal of Genetics, 2018)

Hydrological response of biological soil crusts to global warming: A ten‐year simulative study - Xin‐Rong Li; Rong‐Liang Jia; Zhi‐Shan Zhang; Peng Zhang; Rong Hui (Global Change Biology, 2018)
Biological soil crusts across the desert regions play a key role in regional ecological security and ecological health. They are vital biotic components of desert ecosystems that maintain soil stability, fix carbon and nitrogen, influence the establishment of vascular plants, and serve as habitats for a large number of arthropods and microorganisms, as well as influencing soil hydrological processes. Changes in temperature and precipitation are expected to influence the functioning of desert ecosystems by altering biotic components such as the species composition of biological soil crusts. However, it remains unclear how these important components will respond to the prolonged warming and reduced precipitation that is predicted to occur with climate change. To evaluate how the hydrological properties of these biological soil crusts respond to these alterations, we used open‐top chambers over a 10‐year period to simulate warming and reduced precipitation. Infiltration, dew entrapment, and evaporation were measured as surrogates of the hydrological functioning of biological soil crusts. It was found that the ongoing warming coupled with reduced precipitation will more strongly affect moss in crustal communities than lichens and cyanobacteria, which will lead to a direct alteration of the hydrological performance of biological soil crusts. Reductions in moss abundance, surface cover, and biomass resulted in a change in structure and function of crustal communities, decreased dew entrapment, and increased infiltration and evaporation of biological soil crusts in desert ecosystems, which further impacted on the desert soil water balance.

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Effects of enhanced ultraviolet-B radiation, water deficit, and their combination on UV-absorbing compounds and osmotic adjustment substances in two different moss species - Rong Hui; Ruiming Zhao; Guang Song; Yixuan Li; Yang Zhao; Yanli Wang (Environmental Science and Pollution Research, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

An efficient and green reaction of isatins, 3-amino-1-phenyl-2-pyrazolin-5-one (3-amine-1H-pyrazole), and β-diketone in aqueous medium - Zhansheng Wang; Hui Xu; Lirong Yan; Qingyang Li; Liangce Rong (Molecular Diversity, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Complete genome sequence of a Capsicum chlorosis virus in China and the structural variation and evolutionary origin of its S RNA intergenic region - Ying Huang; Hao Hong; Xiao-Hui Zhao; Jia Li; Xiao-Rong Tao (Archives of Virology, 2017)

Phenotypic Variation and Genetic Diversity in the Collections of Erianthus Arundinaceus (Retz.) Jesw. - Xi-Hui Liu; Huan-Zhong Song; Ge-Min Zhang; Wei-Xing Duan; Rong-Hua Zhang; Yang-Rui Li (Sugar Tech, 2017)

The levels of DNGR-1 and its ligand-bearing cells were altered after human and simian immunodeficiency virus infection - Wen-Rong Yao; Dong Li; Lei Yu; Feng-Jie Wang; Hui Xing; Gui-Bo Yang (Immunologic Research, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Stability analysis of slope in strain-softening soils using local arc-length solution scheme - Xiang-rong Wang; Qi-guo Rong; Shu-li Sun; Hui Wang (Journal of Mountain Science, 2017)

Contamination, Fractionation and Biological Risk Related to Metals in Surface Sediments from the Largest Deep Freshwater Lake in China - Hua-Bing Li; Yang-Guang Gu; Rong Wang; Hui-Bin Lu (Archives of Environmental Contamination and Toxicology, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

The association between the ring finger protein 213 (RNF213) polymorphisms and moyamoya disease susceptibility: a meta-analysis based on case–control studies - Xun-Sha Sun; Jun Wen; Jiao-Xing Li; Rong Lai; Yu-Fang Wang; Hui-Jiao Liu; Wen-Li Sheng (Molecular Genetics and Genomics, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

One-step reverse transcription loop-mediated isothermal amplification assay for rapid detection of melon yellow spot virus - Rong Zeng; Li-hui Xu; Shi-gang Gao; Xiu-hong Ni; Chun-lei Chen; Jian-cai Chen; Fu-ming Dai (European Journal of Plant Pathology, 2016)

Effects of light intensity on leaf photosynthetic characteristics, chloroplast structure, and alkaloid content of Mahonia bodinieri (Gagnep.) Laferr. - De-Xin Kong; Yan-Qun Li; Man-Lian Wang; Mei Bai; Rong Zou; Hui Tang; Hong Wu (Acta Physiologiae Plantarum, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Isolation and characterization of the marine algicidal bacterium Pseudoalteromonas S1 against the harmful alga Akashiwo sanguinea - Hong-Ye Sun; Yu Zhang; Hui-Rong Chen; Chang-Xing Hu; Hui Li; Zhang-Li Hu (Marine Biology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Change of Polysaccharide Content and Its Relation with Nitrogen Level in Sugarcane Leaves Under Nitrogen-Fixing Bacteria Inoculation and Nitrogen Supply - Xi-Hui Liu; Hui-Ping Ou; Rong-Zhong Yang; Rong-Hua Zhang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Geochronology, geochemistry, and Sr–Nd–Pb isotopes of Cretaceous granitoids from western Tibet: petrogenesis and tectonic implications for the evolution of the Bangong Meso-Tethys - Qiang-Tai Huang; Zhou-Rong Cai; Bin Xia; Jian-Feng Li; Lian-Ze Xia; Hui-Chuan Liu (International Geology Review, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

The Effect of PSD-93 Deficiency on the Expression of Early Inflammatory Cytokines Induced by Ischemic Brain Injury - Qingxiu Zhang; Hongyu Cheng; Rong Rong; Hui Yang; Qiuhong Ji; Qingjie Li; Liangqun Rong; Gang Hu; Yun Xu (Cell Biochemistry and Biophysics, 2015)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Psychrobacter fjordensis sp. nov., a psychrotolerant bacterium isolated from an Arctic fjord in Svalbard - Yin-Xin Zeng; Yong Yu; Hui-Rong Li; Wei Luo (Antonie van Leeuwenhoek, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Novel calicivirus from a ferret badger (Melogale moschata) in China - Fa-Ming Miao; Yue-Hong Li; Ye Liu; Shou-Feng Zhang; Fu-Chun Miao; Jing-Hui Zhao; Rong-Liang Hu (Archives of Virology, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

SKF-96365 strongly inhibits voltage-gated sodium current in rat ventricular myocytes - Kui-Hao Chen; Hui Liu; Lei Yang; Man-Wen Jin; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Phosphorylation of p38 MAPK mediates aquaporin 9 expression in rat brains during permanent focal cerebral ischaemia - Xiaoyu Wei; Xuxia Ren; Rong Jiang; Hui Li; Fei Gao; Yuqin Chen; Jiaojiao Hou; Xueyuan Liu; Shanquan Sun; Mei Yang (Journal of Molecular Histology, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Immune protective effect of human alpha-1-antitrypsin gene during β cell transplantation in diabetic mice - Lu Yang; Yu-Ting Liao; Xiao-Fei Yang; Li-Wei Reng; Hui Qi; Fu-Rong Li (Immunologic Research, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Over-expression of SlWRKY39 leads to enhanced resistance to multiple stress factors in tomato - Xiao-chun Sun; Yong-feng Gao; Hui-rong Li; Shu-zhang Yang; Yong-sheng Liu (Journal of Plant Biology, 2015)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Studies on the analgesic activities of Jia-Yuan-Qing pill and its safety evaluation in mice - Ye Tian; Li-rong Teng; Jing-jing Song; Qing-fan Meng; Jia-hui Lu; Wei-wei Zhang; Kang Wei; Ning Wang; Di Wang; Le-sheng Teng (Protoplasma, 2014)

Anti-apoptosis effect of polysaccharide isolated from the seeds of Cuscuta chinensis Lam on cardiomyocytes in aging rats - Shou-Li Sun; Li Guo; Ya-Chao Ren; Bing Wang; Rong-Hui Li; Yu-Shan Qi; Hui Yu; Nai-Dan Chang; Ming-Hui Li; Hai-Sheng Peng (Molecular Biology Reports, 2014)

miR-1246 releases RTKN2-dependent resistance to UVB-induced apoptosis in HaCaT cells - Wei Li; Ya-Fen Wu; Rong-Hua Xu; Hui Lu; Cui Hu; Hua Qian (Molecular and Cellular Biochemistry, 2014)

Effects of Icotinib on Advanced Non-Small Cell Lung Cancer with Different EGFR Phenotypes - Huiyun Pan; Rong Liu; Shengjie Li; Hui Fang; Ziwei Wang; Sheng Huang; Jianying Zhou (Cell Biochemistry and Biophysics, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Systemic Evaluation of Hypoxic-Ischemic Brain Injury in Neonatal Rats - Ai-Hua Zhu; Yan-Rong Hu; Wei Liu; Feng Gao; Jian-Xin Li; Li-Hui Zhao; Gang Chen (Cell Biochemistry and Biophysics, 2014)

Functional TRPV and TRPM channels in human preadipocytes - Hui Che; Jianbo Yue; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2014)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Diversity of bacterioplankton in coastal seawaters of Fildes Peninsula, King George Island, Antarctica - Yin-Xin Zeng; Yong Yu; Zong-Yun Qiao; Hai-Yan Jin; Hui-Rong Li (Archives of Microbiology, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

Comments on ‘Influences of the Bermuda High and atmospheric moistening on changes in summer rainfall in the Atlanta, Georgia region, USA ’ - Wenhong Li; Laifang Li; Rong Fu; Yi Deng; Hui Wang (International Journal of Climatology, 2013)
In a recent article, Diem (2012) examined the impact of the North Atlantic Subtropical High ( NASH ) and atmospheric moistening on summer rainfall variability in the Atlanta, Georgia region. In his paper, he indicated that the results concerning the variability of the NASH western ridge discussed in Li et al . (2011) are incorrect. We present new evidence here to show that the comments by Diem (2012) are unjustified; the main conclusions in Li et al . (2011) were drawn according to the data over a 60‐year (1948–2007) and 45‐year (1958–2002) periods of NCEP / NCAR and ERA ‐40 reanalysis, whereas conclusions of Diem (2011) were based upon the trend analysis of a similar but different index of the NASH using sub‐periods of 1948–2009 (since late 1970s). The comment emphases the importance of climate dynamics to study precipitation variability over the Southeastern US and further strengthens the conclusions originally put forth in Li et al . (2011): over the last 60 years (1948–2007), the NASH has shown a significant trend of westward movement, and the meridional movement of the NASH western‐ridge (i.e. its latitudinal change) has enhanced in the recent three decades.

Identification of wheat-Secale africanum chromosome 2Rafr introgression lines with novel disease resistance and agronomic characteristics - Meng-Ping Lei; Guang-Rong Li; Li Zhou; Cheng-Hui Li; Cheng Liu; Zu-Jun Yang (Euphytica, 2013)

Functional transient receptor potential canonical type 1 channels in human atrial myocytes - Yan-Hui Zhang; Hui-Jun Wu; Hui Che; Hai-Ying Sun; Lik-Cheung Cheng; Xin Li; Wing-Kuk Au; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2013)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Curcumin inhibits the metastasis of K1 papillary thyroid cancer cells via modulating E-cadherin and matrix metalloproteinase-9 expression - Chi-Yu Zhang; Li Zhang; Hui-Xin Yu; Jian-Dong Bao; Rong-Rong Lu (Biotechnology Letters, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Permeability and sedimentation characteristics of pleistocene fluvio-glacial deposits in the Dadu river valley, Southwest China - Guo-xiang Tu; Run-qiu Huang; Hui Deng; Yan-rong Li (Journal of Mountain Science, 2013)

Bacterioplankton community structure in the Arctic waters as revealed by pyrosequencing of 16S rRNA genes - Yin-Xin Zeng; Fang Zhang; Jian-Feng He; Sang H. Lee; Zong-Yun Qiao; Yong Yu; Hui-Rong Li (Antonie van Leeuwenhoek, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Diversity of bacteria in surface ice of Austre Lovénbreen glacier, Svalbard - Yin-Xin Zeng; Ming Yan; Yong Yu; Hui-Rong Li; Jian-Feng He; Kun Sun; Fang Zhang (Archives of Microbiology, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

Meta-analysis of the Association Between DCDC2 Polymorphisms and Risk of Dyslexia - Rong Zhong; Beifang Yang; Hui Tang; Li Zou; Ranran Song; Ling-Qiang Zhu; Xiaoping Miao (Molecular Neurobiology, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Changes in labile soil organic matter fractions following land use change from monocropping to poplar-based agroforestry systems in a semiarid region of Northeast China - Rong Mao; De-Hui Zeng; Lu-Jun Li; Ya-Lin Hu (Environmental Monitoring and Assessment, 2012)

Protective effect of whey protein hydrolysates against hydrogen peroxide-induced oxidative stress on PC12 cells - Qiu-Xiang Zhang; Yu-Fang Ling; Zhen Sun; Li Zhang; Hui-Xin Yu; Samuel Mburu Kamau; Rong-Rong Lu (Biotechnology Letters, 2012)

Cloning, Characterization and Functional Analysis of a Phenylalanine Ammonia-lyase Gene (FtPAL) from Fagopyrum tataricum Gaertn - Cheng Lei Li; Yue Chen Bai; Hui Chen; Hai Xia Zhao; Ji Rong Shao; Qi Wu (Plant Molecular Biology Reporter, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Recombinant human endostatin inhibits adjuvant arthritis by down-regulating VEGF expression and suppression of TNF-α, IL-1β production - Wei Hu; Li-Juan Xia; Fei-Hu Chen; Fan-Rong Wu; Jie Tang; Cun-Zhi Chen; Sheng Jiang; Hui-Hui Chen (Inflammation Research, 2012)

Effects of diagenesis on the acoustic velocity of the Triassic oolitic shoals in the Yudongzi outcrop of Erlangmiao area, Northwest Sichuan Basin - Hui Rong; Yangquan Jiao; Liqun Wu; Yuan Gu; Liya Zhang; Rong Li; Fanping Zeng (Journal of Earth Science, 2012)

Reef types and sedimentation characteristics of Changxing formation in Manyue-Honghua Section of Kaixian, Northeastern Sichuan Basin - Liqun Wu; Yangquan Jiao; Hui Rong; Rui Wang; Rong Li (Journal of Earth Science, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

PNAS-4 expression and its relationship to p53 in colorectal cancer - Bin Zhou; Hui Yan; Yuan Li; Rong Wang; Keling Chen; Zongguang Zhou; Xiaofeng Sun (Molecular Biology Reports, 2012)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Granaticins and their biosynthetic gene cluster from Streptomyces vietnamensis: evidence of horizontal gene transfer - Ming-Rong Deng; Jun Guo; Xiang Li; Chun-Hua Zhu; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2011)

Effects of sediment size on transport capacity of overland flow on steep slopes - Guang-Hui Zhang; Li-Li Wang; Ke-Ming Tang; Rong-Ting Luo; X. C. Zhang (Hydrological Sciences Journal, 2011)

Fresh root decomposition pattern of two contrasting tree species from temperate agroforestry systems: effects of root diameter and nitrogen enrichment of soil - Rong Mao; De-Hui Zeng; Lu-Jun Li (Plant and Soil, 2011)

Changes in soil biochemical properties associated with Ligularia virgaurea spreading in grazed alpine meadows - Xiao Ming Shi; Xiao Gang Li; Rong Mei Wu; Yun Hui Yang; Rui Jun Long (Plant and Soil, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Bacillus beringensis sp. nov., a psychrotolerant bacterium isolated from the Bering Sea - Yong Yu; Hui-Rong Li; Yin-Xin Zeng; Bo Chen (Antonie van Leeuwenhoek, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Sequence Analysis of the Lactoferrin Gene and Variation of g.7605C→T in 10 Chinese Indigenous Goat Breeds - Jing-Fen Kang; Xiang-Long Li; Hui-Qin Zheng; Rong-Yan Zhou; Lan-Hui Li; Hong-Yuan Zhao (Biochemical Genetics, 2011)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Construction and characterization of a full-length infectious clone from a fast-replicating, X4-tropic HIV-1 subtype B′ isolate - Shou-li Wu; Yan-sheng Yan; Ping-ping Yan; Hai-long Huang; Hui-rong Wang (Archives of Virology, 2010)

Genetic Polymorphisms of the CACNA2D1 Gene and Their Association with Carcass and Meat Quality Traits in Cattle - Guan-Yu Hou; Zheng-Rong Yuan; Xue Gao; Jun-Ya Li; Hui-Jiang Gao; Jin-Bao Chen; Shang-Zhong Xu (Biochemical Genetics, 2010)

Soil microbial properties under N and P additions in a semi-arid, sandy grassland - Lu-Jun Li; De-Hui Zeng; Zhan-Yuan Yu; Zhi-Ping Fan; Rong Mao (Biology and Fertility of Soils, 2010)

Soil organic carbon and nitrogen stocks in an age-sequence of poplar stands planted on marginal agricultural land in Northeast China - Rong Mao; De-Hui Zeng; Ya-Lin Hu; Lu-Jun Li; Dan Yang (Plant and Soil, 2010)

Improvement of heat and drought photosynthetic tolerance in wheat by overaccumulation of glycinebetaine - Gui-Ping Wang; Zhen Hui; Feng Li; Mei-Rong Zhao; Jin Zhang; Wei Wang (Plant Biotechnology Reports, 2010)

Expression of a bee venom phospholipase A2 from Apis cerana cerana in the baculovirus-insect cell - Li-rong Shen; Mei-hui Ding; Li-wen Zhang; Wei-guang Zhang; Liang Liu; Duo Li (Journal of Zhejiang University-SCIENCE B, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Alternative splicing in exon 9 of glucocorticoid receptor pre-mRNA is regulated by SRp40 - Xue-Bo Yan; Chen-Hong Tang; Yan Huang; Hui Fang; Zhi-Qiang Yu; Li-Min Wu; Rong-Yu Liu (Molecular Biology Reports, 2010)

Sequencing of Part of the Goat agouti Gene and SNP Identification - Xiang-long Li; Jing-wen Zhao; Chun-juan Tang; Rong-yan Zhou; Guiru Zheng; Lan-hui Li; Xiu-li Guo (Biochemical Genetics, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Erratum to: Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2009)

Liquid-based cytology aids in primary fallopian tube cancer diagnosis - Zhuo Ren; Yun-ping Zhang; Hui-xia Yang; Li-rong Zhu (Journal of Zhejiang University-SCIENCE B, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

Relationships between thiopurine S-methyltransferase polymorphism and azathioprine-related adverse drug reactions in Chinese renal transplant recipients - Hua-Wen Xin; Hui Xiong; Xiao-Chun Wu; Qing Li; Lei Xiong; Ai-Rong Yu (European Journal of Clinical Pharmacology, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

One-step preparation of antibody and oligonucleotide dual-labeled gold nanoparticle bio-probes and their properties - Xiao-li Kong; Fei-yan Qiao; Hui Qi; Fu-rong Li (Biotechnology Letters, 2008)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Application of NIR spectroscopy for firmness evaluation of peaches - Xia-ping FU; Yi-bin Ying; Ying Zhou; Li-juan Xie; Hui-rong Xu (Journal of Zhejiang University-SCIENCE B, 2008)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Effects and complications of placement of motility coupling post in porous polyethylene orbital implants - Hong-guang Cui; Rong-rong Hu; Hui-yan Li; Wei Han (Journal of Zhejiang University-SCIENCE B, 2008)

Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Bioenergetic Investigation of Action of Lithium to Tetrahymena thermophila bF5 by Microcalorimetry - Hui-Rong Li; Yi Liu; Cai-Qin Qin; Qiang-Guo Li (Biological Trace Element Research, 2007)

Effects of biological soil crusts on emergence of desert vascular plants in North China - Yan-Gui Su; Xin-Rong Li; Ying-Wu Cheng; Hui-Juan Tan; Rong-Liang Jia (Plant Ecology, 2007)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

Passage number affects the pluripotency of mouse embryonic stem cells as judged by tetraploid embryo aggregation - Xiang-yun Li; Qing Jia; Ke-qian Di; Shu-min Gao; Xiao-hui Wen; Rong-yan Zhou; Wei Wei; Li-ze Wang (Cell and Tissue Research, 2007)

Apelin suppresses apoptosis of human osteoblasts - Hui Xie; Ling-Qing Yuan; Xiang-Hang Luo; Jiao Huang; Rong-Rong Cui; Li-Juan Guo; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (Apoptosis, 2007)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Abnormal pollen development of bread wheat-Leymus mollis partial amphiploid - Xing-Feng Li; Shu-Bing Liu; Ju-Rong Gao; Wen-Hui Lu; Hong-Gang Wang (Euphytica, 2005)

Molecular Cloning and Expression of IL2 cDNA from the Tibet Pig - Li Hui; Gao Rong; Wu Mei; Wang Li-Huan; Fu Man-Liang; Wu Kai-Yuan (Veterinary Research Communications, 2005)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Ile118Val genetic polymorphism of CYP3A4 and its effects on lipid-lowering efficacy of simvastatin in Chinese hyperlipidemic patients - An Wang; Bang-Ning Yu; Chen-Hui Luo; Zhi-Rong Tan; Gan Zhou; Lian-Sheng Wang; Wei Zhang; Zhi Li; Jie Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2005)

Conversion rates of surface HOx radicals in Beijing City - Xin-rong Ren; Li-xin Wang; Hui-xiang Wang; Guo-fang Miao (Chinese Geographical Science, 2004)

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)